P01.18 Metabolic status and immune activation influence clinical outcomes in patients after allogeneic hematopoietic stem cell transplantation. (1st October 2020) - Althoff, K; Leitzke, S; Herling, C; Frenzel, L; Herling, M; Holtick, U; Scheid, C; von Bergwelt-Baildon, M; Theurich, S
Abstract : Background: The nutritional status is an important factor contributing to non-relapse mortality for patients undergoing allogeneic hematopoietic stem cell transplantation (alloHSCT). In contrast to underweight, the role of overweight and obesity for alloHSCT outcomes is less well understood. This might be due to the use of the body-mass-index (BMI) as a classic measure of metabolic risk, which does not necessarily reflect body composition and visceral obesity. Importantly increased inflammation and malnutrition (Glasgow-Prognosis-Score, GPS) as well as increased neutrophil-to-lymphocyte ratios (NLR) have been described as adverse prognostic factors for a variety of solid tumors. In alloHSCT the GPS and NLR are ill defined so far. Here, we analyzed the impact of pretransplant GPS and d+100 NLR in correlation to the BMI on clinical outcomes following alloHSCT. Materials and Methods: Clinical data of consecutively treated patients between 2012 and 2017 at our transplant center were analyzed. From these cases only matched (10/10) related and unrelated donors and reduced intensity conditionings were included into the analysis. Based on BMI and GPS prior to conditioning we defined three groups respectively: normal weight (NW), overweight (OW), obese (OB); and GPS 0 (CRP<10 mg/dl, normal protein), GPS 1 (CRP >10 mg/dl, normal protein), GPS 2 (CRP >10 mg/dl, low protein). NLR at d+100 were also analyzed. We focused on survival and mortality until the data lock. Incidence rates of acute graft-versus-host disease (aGvHD) were determined until day+100. Results: From a total of 464 identified records, 265 cases were included into the analysis based on the inclusion criteria. Median overall survival in OB patients was doubled compared to NW (48 vs. 21.8 months; p=0.01) and in OW patients median overall survival was not reached (figure 1, not included in the submitted abstract). Pretransplant GPS could also dissect survival curves with worst OS for patients with GPS 2: 9 (GPS 2) vs. 25.6 (GPS 1) vs. 48 (GPS 0) months, p=0.007). However, GPS values did not correlate with BMI (figure 2, not included in the submitted abstract). Increased d+100 NLR correlated non-significantly with poorer survival and increased relapse rates. There was a trend to increased clinically relevant aGvHD (≥II°) in GPS 2 individuals, not detectable according to BMI groupings. Conclusions: There is a need for better immunometabolic risk measures in patients before alloHSCT. Our data suggest that pretransplant GPS and NLR could be of value for risk estimations and further validation is warranted. Disclosure Information: K. Althoff: None. S. Leitzke: None. C. Herling: None. L. Frenzel: None. M. Herling: None. U. Holtick: None. C. Scheid: None. M. von Bergwelt-Baildon: None. S. Theurich: None.